98 ORAL ANTICOAGULANT THERAPY AND RISK OF MACE IN ELDERLY PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION: REAL WORLD EVIDENCE DATA. (15th December 2022) - Armentaro, Giuseppe; Condoleo, Valentino; Divino, Marcello; Pastura, Carlo Alberto; Francica, Mattea; Barbara, Keti; Monaco, Vittoria; Clausi, Elvira; Scarcelli, Maria Rosangela; Cuda, Patrizia; Severini, Giandomenico; Marco, Mario De; et al.
Abstract: Aim: Atrial fibrillation (AF) is the most common cardiac arrhythmia globally and is associated with a five-fold increased risk of stroke compared with patients without AF. Although large clinical trials have demonstrated the noninferiority of NOACs to VKAs in preventing stroke and systemic thromboembolism and their use is recommended by the guidelines, the role of antithrombotic therapies on the risk of major adverse cardiac events (MACE) in a high-risk population, such as the elderly, is still controversial (2). The aim of this work is to evaluate any differences on the occurrence of MACE among NOACs-treated patients versus VKAs in an elderly population with AF and other critical comorbidities. Materials and Methods: 420 caucasian patients with non-valvular AF, aged ≥65 years were enrolled, 136 in treatment with VKAs and 284 with NOACs, with mean age 76.7±5.7. A clinical-instrumental and laboratory evaluation was performed for a follow-up of 93.9 months. Statistical analysis was performed with Wicoxon's test, Student's t-test, log rank test, univariate and multivariate Cox regression model in order to calculate the hazard ratio (HR) for independent predictors associated with the incidence of MACE. Results: The two groups were overlappings for sex, smoking, T2DM. NOACs group had a higher prevalence of: HF (110 vs 32, p=0.002), COPD (127 vs 39 p = 0.001), arterial hypertension (266 vs 112, p = 0.0003) and they were older than VKAs group (78.4±4.7 vs 73.2±5.9 years; p<0.0001). In the whole general population at baseline, the following values ​​were detected: estimated glomerular filtration rate (eGFR) 64.6 ± 18.2 ml/min/1.73 m 2, Systolic blood pressure (BP)132.5±11.6 mmHg, diastolic BP 76.6±9.5 mmHg, BMI 29.4±4.8 Kg/m 2 . In patients treated with NOACs, MACEs observed were 44 (2.4 events /100 patient-years), while in the group treated with VKAs were 76 (7.2 events/100 patient-years) (p <0.0001). A multivariate analysis model showed that an enhancement of 1g/dl of albuminemia value (HR 0.565, p=0.033), taking a therapy with β-blockers (HR 0.621, p=0.013), ACE inhibitors or ARBs (HR 0.695, p=0.024) were protective factors for the onset of MACE, while VKAs therapy (HR 2.596, p<0.0001) and HF (HR 1.471, p<0.0001) increased the risk of MACE in patients with AF. Conclusions: The data of present study confirm a better safety profile of NOACs compared to VKAs on the occurrence of MACE in an elderly population with critical comorbidities, even though patients treated with NOACs were older and had a greater burden of comorbidities that negatively affect the risk of MACE such as: arterial hypertension, COPD and heart failure.